The Countermeasures Against Alcohol Abuse in Central Buntulia - Viergiawan Makmur (Universitas Negeri Gorontalo, 2019)
The use of liquor in Central Buntulia is still a bad habit that is often practiced by children, teenagers, and adults. The cause of liquor in the Central Buntulia environment is one of the problems that are troubling to the surrounding community, as well as to people who visit it because many people do not care about the bad effects of liquor which is very dangerous and detrimental. This research aims to know the prevention of liquor in Central Buntulia. Based on the title raised in this article, the researcher uses the type of empirical research. The process of collecting data from the object studied in this study is to use observation techniques, interviews, and literature study so that the data obtained by the researcher was analyzed descriptively. The results of the study showed that there were several countermeasures against liquor in Central Buntulia, starting from the efforts of the village government to the efforts of the police.